Are Perceived Effort Scales (OMNI-RES) Appropriate for Defining and Controlling Strength Training Intensity? - José Luis Maté-Muñoz; Luis Maicas-Pérez; Iñigo Aparicio-García; Juan Hernández-Lougedo; Luis De Sousa-De Sousa; Mónica Hontoria-Galán; Francisco Hermosilla-Perona; Manuel Barba-Ruiz; Pablo García-Fernández; Juan Ramón Heredia-Elvar (Sports)
Background: One of the most significant challenges for exercise professionals in designing strength training programs is determining the intensity or effort level of each set performed. One of the most studied methodologies has been the use of Rate of Perceived Exertion (RPE) scales. This study aims to analyze the application of the OMNI-RES scale for monitoring training intensity across different relative loads and fatigue levels in various training protocols. Methods: In this cross-sectional study, participants completed nine exercise sessions, with one week separating each session. The first session involved a one-repetition maximum (1RM) test in the bench press (BP) to identify the load–velocity relationship. Subsequently, each participant randomly performed two maximum repetition (MNR) protocols at 60% and 90% of 1RM, and two protocols with a 30% velocity loss (VL) at 60% of 1RM and a 10% VL at 90% of 1RM. These sessions were repeated one week later. Results: significant differences were found between the four bench press protocols regarding the number of repetitions and the percentage of velocity loss per set (p < 0.001). However, the RPE of the MNR protocol at 60% of 1RM was significantly higher than the other protocols. Moreover, the RPE for the protocol at 60% of 1RM with a 30% VL was similar to that at 90% of 1RM with a 10% VL (p = 1.000). Post-exercise blood lactate concentrations, percentage VL at 1 m·s−1, and the effort index were significantly higher in the MNR protocol at 60% of 1RM compared to all other protocols (p < 0.001). Conclusions: The most important finding of this study is that the OMNI-RES scale may not be a reliable indicator of exercise intensity. This is because the highest values on the scale were observed at the lowest relative intensity (60% 1RM) during the maximum number of repetitions (MNR) protocol, corresponding to the maximum volume.